Optimization of the extraction of bioactive compounds from Pouzolzia zeylanica using Box-Behnken experimental design and application in the preparation of mixed juice - THUY, Nguyen Minh; THANH, Nguyen Van; VY, Vo Ngoc Tuong; GIAU, Tran Ngoc; TIEN, Vo Quoc; TAI, Ngo Van; MINH, Vo Quang (Food Science and Technology, 2023)
Pouzolzia zeylanica grows naturally in the forest and is quite popular in Vietnam. This study was designed to investigate the influence of extraction parameters and their effective application in the processing of mixed fruit juice from P. zeylanica and orange juice. A three-factor [i.e., solvent ratio and material (5:1–6:1), extraction temperature (85–95 °C), and extraction time (10–15)] and three-level Box-Behnken design consisting of 18 experimental runs with 6 center points was used for the extraction of P. zeylanica. The optimal conditions (maximum extraction yield) based on both individual and combinations of all responses (ratio of water: materials is 5.4:1 v/w, extraction temperature 91 °C, and time 13 min) were found. At these optimum conditions, the TAC and TPC were found to be 13.55 mg/L and 88.26 mgGAE/L with a desirability value of 0.91. The experimental values are in close agreement with the corresponding predicted values (R2=0.942). In addition, by adding orange juice as a natural ingredient that provides additional vitamin C, this study attempted to improve the mixed juice product quality and increase antioxidant capacity and organoleptic value. The mixed juice with the ratio of P. zeylanica extract and orange juice of 80% and 20%, respectively, for a product with high TPC and TAC contents (240.61 mgGAE/L and 10.84 mg/L), significantly improved vitamin C content (255.96 mg/L) and antioxidant activity (67.55% DPPH).